2005
DOI: 10.1007/bf03027741
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic response to moderate dobutamine dose in OPCAB during acute normovolemic hemodilution

Abstract: Hemodynamic response to moderate dobutamine dose in OPCAB during acute normovolemic hemodilutionTo the Editor: Acute normovolemic hemodilution (ANH) is a widespread practice during coronary artery surgery and numerous studies emphasize the safety of a low transfusion trigger in these patients. [1][2][3] During off-pump coronary artery bypass surgery (OPCAB), periods of hemodynamic instability that require inotropic therapy may occur. 4 However, no studies, except experimental, evaluate how hemodilution influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…11 However, any increase in myocardial O 2 demand in these conditions could be associated with the development of myocardial ischemia and cardiac dysfunction. Tonkovic et al 38 recently assessed before surgery the hemodynamic response to moderate dobutamine doses in hemodiluted CAD patients scheduled for off-pump surgery. Patients were hemodiluted to a target hemoglobin concentration of either 9.5 to 10.5 g/dL (moderate ANH) or 7.5 to 8.5 g/dL (severe ANH).…”
Section: Anh and Coronary Artery Diseasementioning
confidence: 99%
“…11 However, any increase in myocardial O 2 demand in these conditions could be associated with the development of myocardial ischemia and cardiac dysfunction. Tonkovic et al 38 recently assessed before surgery the hemodynamic response to moderate dobutamine doses in hemodiluted CAD patients scheduled for off-pump surgery. Patients were hemodiluted to a target hemoglobin concentration of either 9.5 to 10.5 g/dL (moderate ANH) or 7.5 to 8.5 g/dL (severe ANH).…”
Section: Anh and Coronary Artery Diseasementioning
confidence: 99%
“…12 Dans le présent numéro, Tonkovic et coll. 13 ont évalué la réponse hémodynamique à des doses modérées de dobutamine chez des patients devant subir une opération de pontages coronaire à coeur battant. Les patients étaient sous hémodilution selon un taux cible de 95 à 105 g•L -1 [hémodilution normovolémique aiguë modérée (HNA)] ou de 75 à 85 g•L -1 (HNA sévère).…”
Section: Le Coeur Et L'hémodilution Normovolémiqueunclassified
“…Cardiovascular disease patients with a lower preoperative hematocrit have an increased risk of death when compared to non-cardiovascular disease patients with the same preoperative hematocrit. 12 In the present issue, Tonkovic et al 13 evaluated the hemodynamic response to moderate dobutamine doses in hemodiluted coronary artery disease patients scheduled for off-pump surgery. Patients were hemodiluted to a target hemoglobin of either 95 to 105 g•L -1 [moderate acute normovelemic hemodilution (ANH)] or 75 to 85 g•L -1 (severe ANH).…”
mentioning
confidence: 99%
“…As heart rate is a major determinant of the myocardial oxygen balance, tolerance to acute isovolaemic haemodilution may closely depend on the heart rate [1]. Several studies in volunteers and patients have indeed demonstrated that increased heart rate was associated with a decreased tolerance of the heart to haemodilution [2–4].…”
mentioning
confidence: 99%